OVX033, a nucleocapsid-based vaccine candidate, provides broad-spectrum protection against SARS-CoV-2 variants in a hamster challenge model - Primard, Charlotte; Monchâtre-Leroy, Elodie; Del Campo, Judith; Valsesia, Séverine; Nikly, Elsa; Chevandier, Marion; Boué, Franck; Servat, Alexandre; Wasniewski, Marine; Picard-Meyer, Evelyne; Courant, Thomas; Collin, Nicolas; et al. (Frontiers in Immunology, 2023)
Spike-based COVID-19 vaccines induce potent neutralizing antibodies but their efficacy against SARS-CoV-2 variants decreases. OVX033 is a recombinant protein composed of the full-length nucleocapsid (N) protein of SARS-CoV-2 genetically fused to oligoDOM®, a self-assembling domain which improves antigen immunogenicity. OVX033 including N as an antigenic target is proposed as new vaccine candidate providing broad-spectrum protection against sarbecoviruses. OVX033 demonstrated its ability to trigger cross-reactive T cell responses and cross-protection against three variants of SARS-CoV-2 (B.1 Europe, Delta B.1.617.2, and Omicron B.1.1.529) in a hamster challenge model, as evidenced by lower weight loss, lower lung viral loads, and reduced lung histopathological lesions.